2010
DOI: 10.3923/pjbs.2010.148.151
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity Test for Extracts of Sarang Semut Plant (Myrmecodya pendens) to HeLa and MCM-B2 Cells

Abstract: The aim of this study is to investigate anticancer activity of methanol extract (ethylacetate, n-buthanol and water partitions) and water extract from Sarang semut (local name), Myrmecodya pendens which is one of Rubiaceae family. Within Papua area (Indonesia), this medicinal plant has been used traditionally as alternative treatment for ulcer, tumor and cancer. In this study, the extracts of this plant were tested for their activities in some cancer cells (HeLa and MCM-B2 cell). The result showed that water e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 8 publications
1
66
0
8
Order By: Relevance
“…A phytochemical study of Sarang Semut reported active phenolic compounds found in ethanol 70% extract and boiling water extract including flavonoids, tannin, phenolic, and alkaloid [7]. Other study showed that water extract of Sarang Semut contains flavonoid compounds, saponin, glycoside, and tannin; while the n-butanol extract contains flavonoids, tannins, and quinons; and the ethyl acetate extract contains only flavonoids and tannins [8]. Flavonoid compounds were also found in ethyl acetate, methanol, as well as ethanol extract and also in ethyl acetate fraction as well as n-hexane fraction of Sarang Semut [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A phytochemical study of Sarang Semut reported active phenolic compounds found in ethanol 70% extract and boiling water extract including flavonoids, tannin, phenolic, and alkaloid [7]. Other study showed that water extract of Sarang Semut contains flavonoid compounds, saponin, glycoside, and tannin; while the n-butanol extract contains flavonoids, tannins, and quinons; and the ethyl acetate extract contains only flavonoids and tannins [8]. Flavonoid compounds were also found in ethyl acetate, methanol, as well as ethanol extract and also in ethyl acetate fraction as well as n-hexane fraction of Sarang Semut [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Sarang Semut is a member of Rubiaceae family, which two genus are naturally become ant nest (Sarang Semut) including Myrmecodia (45 species) and Hypnophytum (26 species) [8]. Some studies have proven the efficacy of Sarang Semut in different cancer entities, including breast, uterus, tongue, and oral cancer [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myrmecodia Pendans (in Indonesia called Sarang Semut) is a plant that has a high antioxidant activity [3]. In previous studies, sarang semut shown to contain flavanoids after tested using HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Flavonoids as antibacterial, antiinflammatory and antioxidant, antibacterial saponins, tannins as a hemostatic and astringent and alkaloids as an analgesic. 13,14 The aim of this study was to determine the effect of ethanol extract of the root of sarang semut as formulation of granulation tissue on wound healing after tooth extraction.…”
Section: Introductionmentioning
confidence: 99%